Serial Glycolic Acid Peels Verses Topical Adapalene Gel in the Treatment of Melasma - Uzma DM Rajar, Navaid Kazi, Salman Farsi Kazi , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2015)
Objective: The study aimed to access the efficacy and safety of serial glycolic acid peels verses topical adapalene gel in melasma. Study Design: Prospective, randomized trial, Place and Duration: Department of Dermatology, Isra University, Hyderabad. during May 2014 -December 2014, Material & Methods: Sixty patients with melasma were enrolled in this prospective, randomized trial, and divided into two groups; the Group A received chemical peels of serial glycolic acid peels. The Group B received topical adapalene gel at night. The clinical improvement was assessed with the Melasma Area Severity Index (MASI) at baseline and every six weeks during the 30-week treatment period, the observations were analysed and results were tabulated. Results: The results showed a prominent decrease in MASI scores at the end of the treatment in both groups, the results were better in the Group A receiving chemical peels (P= 0.048). All patients tolerated the topical agents well with minimal irritation observed in the first few weeks of the therapy. Conclusion: Study suggests that treatment with serial glycolic acid peels should be considered as an effective and safe therapy in melasma.